2020
DOI: 10.3390/ijms21072347
|View full text |Cite
|
Sign up to set email alerts
|

Brain–Heart Axis and Biomarkers of Cardiac Damage and Dysfunction after Stroke: A Systematic Review and Meta-Analysis

Abstract: Background: Cardiac complications after a stroke are the second leading cause of death worldwide, affecting the treatment and outcomes of stroke patients. Cardiac biomarkers such as cardiac troponin (cTn), brain natriuretic peptide (BNP), and N-terminal pro-brain natriuretic peptide (NT-proBNP) have been frequently reported in patients undergoing a stroke. The aim of the present study is to meta-analyze the relationship between changes in such cardiac biomarkers and stroke and to present a systematic review of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 90 publications
(130 reference statements)
0
16
0
Order By: Relevance
“…Thus, it is indicated that the prognosis of AIS patients with increased monocyte number at admission may be more difficult than in other patients, as indicated by the results of the present study. Previous findings revealed the multiple effects of HDL-cholesterol (antithrombotic, antioxidant and anti-inflammatory), which has a role of inhibiting the endothelial expression of adhesion molecules, impeding monocyte adherence to the arterial wall (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is indicated that the prognosis of AIS patients with increased monocyte number at admission may be more difficult than in other patients, as indicated by the results of the present study. Previous findings revealed the multiple effects of HDL-cholesterol (antithrombotic, antioxidant and anti-inflammatory), which has a role of inhibiting the endothelial expression of adhesion molecules, impeding monocyte adherence to the arterial wall (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…In order to establish additional diagnosis and identify patients with increased risk of cardiac events, the biochemical analysis of brain natriuretic peptide (BNP), cTn and N-terminal BNP (NT-proBNP) (indicators revealing myocardial damage in stroke) was indicated. The cardiac biomarkers need to be attentively monitored, focusing on the therapy of cerebrovascular impairments, to offer immediate and proper treatment (24).…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of brain disease, including cerebrovascular diseases, degenerative diseases of the nervous system, and infectious diseases of the central nervous system, can lead to myocardial injury and even cardiac dysfunction, which is described as the brain-heart axis [ 2 4 ]. On the other hand, the physiological activities and processes of the brain, such as cognitive ability and language capabilities, are directly affected by cardiac function, which is described as the heart-brain axis [ 5 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism consists of abnormal upregulation of the hypothalamic–pituitary–adrenal axis, autonomic nervous system upregulation, and catecholamine surge, as well as gut microbiome and systemic immunological reactions against inflammation [ 19 , 20 ]. Biomarkers of cardiac damage and dysfunction after stroke have also been investigated, and the amino-terminal fragment of probrain natriuretic peptide (NT-proBNP) might be one of the best markers for cardiac damage after stroke [ 117 ]. Interestingly, epidemiological studies have shown that circulating concentrations of the BDNF protein are lowered in the acute phase of ischemic stroke, and low levels are associated with a poor functional outcome and mortality [ 118 , 119 ].…”
Section: Pathophysiological Role Of Nts In Cardiovascular Abnormalities Associated With Neurological Diseasesmentioning
confidence: 99%